2D Co-based coordination polymer with a histidine derivative as an efficient heterogeneous catalyst for the oxidation of cyclohexene. Issue 15 (31st March 2017) - Yu, Fan; Xiong, Xin; Huang, Kexing; Zhou, Yinliu; Li, Bao
Abstract : Utilizing a histidine derivative as an organic linker, a 2D cobalt-based coordination polymer has been constructed that shows high catalytic activity in the allylic oxidation of cyclohexene toward formation of tert -butyl-2-cyclohexenyl-1-peroxide. Abstract : The hydrothermal reaction of CoCl2 and 4-((1-carboxy-2-(1 H -imidazol-4-yl)ethylamino)methyl)benzoic acid (H2 L) generated a Co2 (H2 O)-based 2D coordination framework, (Co(L)(H2 O))2 (H2 O) n (1 ). Heterogeneous catalytic experiments on the allylic oxidation of cyclohexene show that activated1 exhibits high catalytic activity using tert -butylhydroperoxide ( t -BuOOH) as the oxidant toward the formation of tert -butyl-2-cyclohexenyl-1-peroxide. The activation energy for the oxidation of cyclohexene with catalyst1 was approximately calculated as 91.98 kJ mol −1 . This work demonstrates that a degree of creativity in the coordinatively unsaturated metal sites in CPs could significantly enhance their heterogeneous catalytic activity and selectivity.